The Salvation of Europe is (Found) in Beauty? - Ivan Djeparoski (Kultura (Skopje), 2014)
In this essay Dostoevsky’s famous utterance, “Beauty will save the world”, from his novel The Idiot (1869) is being analyzed, namely, by examining the interpretations of this utterance in the works of Solovyov and Solzhenitsyn. The essay also treats the problem of the old philosophical and aesthetical question about the unity of beauty, goodness, and truth, and in the end, it stresses the changes that occurred in the way beauty was comprehended in the 20th century. The paper also sets out to analyze some of the questions tied to the lost place of beauty nowadays, by offering a possible (affirmative) answer to the welcomed return of the meaning and the significance of beauty for our contemporary culture and art.